Reprogramming the Tumor Ecosystem via Computational Intelligence-Guided Nanoplatforms for Targeted Oncological Interventions - Jadhav, Sachin; Aruna, Chittineni; Choudhary, Vijay; Gamini, Sridevi; Kapila, Dhiraj; Reddy, C. S. Preetham (Trends in Immunotherapy, 2025)
The Tumor Microenvironment (TME) resists conventional treatments by sending out signals that weaken the immune system. Tumor cells vary significantly, and treatments can lead to resistance. This paper focuses on constructing an effective module for reprogramming the tumor ecosystem using Computational Intelligence-Guided Nanoplatforms. It hypothesizes that computationally optimized fuzzy deep learning, integrated with nanoplatform-mediated drug delivery, can dynamically reprogram tumor-infiltrating T-cells to overcome immunosuppression in the TME, thereby enhancing cytotoxicity and therapeutic response. A novel nanotechnology-integrated deep fuzzy learning framework—Seagull Optimized Sugeno Fuzzy Deep Learning (SgOSF-DL)—is proposed to reprogram T-cell behavior in real-time. Multi-omic data from tumor-infiltrating T-cells are encoded and analyzed using fuzzy logic to determine their immune state (suppressed, exhausted, or active), guided by key biomarkers such as Granzyme B and PD-1. The optimized model governs the release of IL-21 and checkpoint inhibitors via nanoplatforms composed of PLGA, gold nanoshells, and iron oxide particles. Fuzzy rules are formulated using optimized parameters to evaluate the TME. Simulation results confirm that the proposed SgOSF-DL model accurately distinguishes between cancer and healthy cells. It alters cancer behavior by reducing tumor burden, lowering PD-1, and boosting Granzyme B expression. The model achieves 96.5% accuracy in classifying T-cell states, reduces tumor count by 69.2%, and decreases PD-1 expression by 61% for active immune function. It also offers faster therapeutic classification (0.017 seconds) with an activation consistency of 92.8%. Fuzzy logic enables transparent decision-making, aiding clinicians in understanding the treatment rationale.